2020
DOI: 10.1016/j.ekir.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Prospective Study Comparing Anti–T-Lymphocyte Igs to Basiliximab in Highly Sensitized Kidney Transplant Patients

Abstract: Background: Two prospective studies that were performed before the era of highly sensitive solid-phase assays have shown a lower incidence of acute rejection in highly sensitized kidney-transplant patients given polyclonal antibodies compared with those given anti-CD25 monoclonal antibodies. Methods: This prospective pilot randomized French multicenter study aimed to compare anti-T-lymphocyte Ig (ATLG) (n ¼ 32) and basiliximab (n ¼ 27) in highly sensitized kidney-transplant patients without preformed donor-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Using a regimen of 9 mg/kg prior to reperfusion of the allograft, followed by 3 mg/kg/day on day 1 to 4, a randomized study from Switzerland reported ABMR and ACR rate of 35% and 11% within 1 year of transplantation [ 23 ]. With similar dosing regime, Kamar et al observed BPAR and graft loss rate of 3.6% and 9.6% at 1 year [ 15 ]. These data indicate that ATLG is effective in reducing acute rejection and improving graft survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a regimen of 9 mg/kg prior to reperfusion of the allograft, followed by 3 mg/kg/day on day 1 to 4, a randomized study from Switzerland reported ABMR and ACR rate of 35% and 11% within 1 year of transplantation [ 23 ]. With similar dosing regime, Kamar et al observed BPAR and graft loss rate of 3.6% and 9.6% at 1 year [ 15 ]. These data indicate that ATLG is effective in reducing acute rejection and improving graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies from India have shown equivalent patient survival and death-censored graft survival with ATLG and ATG [12]. Compared to basiliximab, ATLG has similar rates of biopsy-proven acute rejection (BPAR) and acute graft rejection [15]. However, rates of delayed graft function and need for dialysis were lower with ATLG than basiliximab [16].…”
Section: Introductionmentioning
confidence: 99%